The Influence of Risk Factors on Perioperative Results of Multivessel Coronary Artery Bypass Grafting Through the Left Anterior Minitoracotomy - Babliak, O. D.; Demianenko, V. M.; Babliak, D. E.; Marchenko, A. I.; Melnyk, E. A.; Revenko, K. A.; Pidgaina, L. V.; Stohov, O. S. (Transplantation and artificial organs, 2021)
Multivessel coronary artery bypass grafting (CABG) through the left anterior minitoracotomy using the technique of total coronary revascularization via left anterior thoracotomy (TCRAT) is routinely performed in our institution since July 2017. This technique is used in all patients regardless of the number of anastomoses, quality and location of coronary targets, body mass index, age, comorbidities and predicted postoperative risk. The aim. To present the results of 349 consecutive patients with isolated multivessel coronary artery disease who underwent minimally invasive CABG. To compare perioperative outcomes of minimally invasive CABG in patients with existent risk factors for CABG and to identify possible contraindications to the use of this CABG technique. Materials and methods. From July 2017 to January 2020, 357 consecutive patients were underwent multivessel CABG at our institution. Eight (2.3%) patients in whom CABG was performed through the median sternotomy were excluded from the study. The remaining 349 (97.7%) patients underwent complete myocardial revascularization through the left anterior minitracotomy using TCRAT technique (peripheral cannulation for cardiopulmonary bypass (CPB), cold blood cardioplegia). All the patients were divided into groups according to the presence of risk factors (obesity, old age, diabetes, risk of postoperative mortality greater than 2.0 calculated by EuroSCORE II scale) to analyze the impact of these factors on intraoperative and postoperative parameters. Results. Intra- and postoperative parameters in patients of all groups were within safe limits. There was no statistically significant difference between the patients older and younger than 70. Diabetic and obese patients had a longer total operation time (on average by 5%, p = 0.003 and 7%, p = 0.019, respectively), CPB time (on average by 8%, p = 0.002 and 11%, p = 0.0001, respectively) and intensive care unit stay (on average by 15%, p = 0.004 and 17%, p = 0.013, respectively) compared to the patients without these conditions. The patients with EuroSCORE II risk more than 2.0 were had longer main phase of the operation (on average by 12 minutes, i.e. 8%, p = 0.013), they required longer ventilation time (by 27%, p = 0.036), longer stay in the intensive care unit (by 23%, p = 0.0004), had a longer hospital stay (by 15%, p < 0.0001), they were more likely to have acute kidney damage that required hemodialysis, and mortality was observed only in this group of patients. However, even in this group of severe patients, the incidence of complications and mortality did not exceed the predicted rates. Conclusions. The technique of minimally invasive CABG through the left anterior thoracotomy allow the possibility to avoid median sternotomy in 97.7% of patients with multivessel coronary artery disease. The technique of minimally invasive multivessel CABG through the left anterior thoracotomy is universal and does not require patient selection, because it can be used effectively and safely regardless of obesity, diabetes or old age. This technique can be performed in patients with any EuroSCORE II rate without the mortality rate increase.